2008
DOI: 10.1007/s11157-008-9131-1
|View full text |Cite
|
Sign up to set email alerts
|

The roles of acetotrophic and hydrogenotrophic methanogens during anaerobic conversion of biomass to methane: a review

Abstract: Among different conversion processes for biomass, biological anaerobic digestion is one of the most economic ways to produce biogas from various biomass substrates. In addition to hydrolysis of polymeric substances, the activity and performance of the methanogenic bacteria is of paramount importance during methanogenesis. The aim of this paper is primarily to review the recent literature about the occurrence of both acetotrophic and hydrogenotrophic methanogens during anaerobic conversion of particulate biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
517
1
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 989 publications
(563 citation statements)
references
References 146 publications
(105 reference statements)
29
517
1
16
Order By: Relevance
“…For these samples, the volume of biogas decreased, and the concentration of CH 4 in the biogas was lower than 60% (Table 3). The function of hydrogenotrophic methanogens is extremely important in the anaerobic use of simple soluble compounds; however, their role in biomass processing of complex organic compounds is poorly understood (Demirel and Scherer, 2008). The samples (FM4-FM7) collected under the longer waste retention times (29-47 days), which are characterised by higher abundance of Methanosaeta, are known to utilise acetate as the only substrate for methanogenesis.…”
Section: Relative Fluorescent Units (Rfu)mentioning
confidence: 99%
“…For these samples, the volume of biogas decreased, and the concentration of CH 4 in the biogas was lower than 60% (Table 3). The function of hydrogenotrophic methanogens is extremely important in the anaerobic use of simple soluble compounds; however, their role in biomass processing of complex organic compounds is poorly understood (Demirel and Scherer, 2008). The samples (FM4-FM7) collected under the longer waste retention times (29-47 days), which are characterised by higher abundance of Methanosaeta, are known to utilise acetate as the only substrate for methanogenesis.…”
Section: Relative Fluorescent Units (Rfu)mentioning
confidence: 99%
“…It was found that the dominant microbes on both anodes of E1 and E2 were hydrogenotrophic methanogens including 5 genus, Methanocorpusculum, Methanospirillum, Methanobacterium, Methanobrevibacter and Methanoculleus [16] (Fig. 2).…”
Section: Mechanisms For Upgraded Biogas Productionmentioning
confidence: 99%
“…Of particular importance is its application to the treatment of animal wastes where it can play a significant role in minimising the uncontrolled emission of methane to the atmosphere, thus reducing the impact of greenhouse gases associated with livestock management. The microbiology of the process relies on a number of interdependencies which allow a variety of complex organic materials to be converted to methane through the processes of hydrolysis, acidogenesis, acetogenesis, hydrogenogenesis and methanogenesis (Demirel & Scherer, 2008).…”
Section: Introductionmentioning
confidence: 99%